Research on the crystallization behavior occurred in the process of preparing bulk metallic glass with selective laser melting. (29th March 2019) - Guo, S; Wang, M; Lin, X; Huang, W D
Abstract: The crystallization behavior occurred in the heat affected zone in the process of bulk metallic glasses preparation with selective laser melting has been studied with molecular dynamics simulation. Cyclical heating conditions are applied with three different temperature variation rates in the simulation cases, while the heating rate is ten times of the cooling rate in each case. The results reveal that the newly formed crystal cluster has more Ni atoms than the parent phase. When the cooling rate is about one third of the critical cooling rate for the formation of metallic glass, the crystallization behaviors happen in the first cooling process, which is controlled alternately by growth mechanism and nucleation mechanism. In the following heating process, the numbers of both crystal clusters and crystal atoms first increase and then decrease. When the cooling rate is about two fifths of the critical cooling rate, the crystallization behaviors happen in the second cooling process. When the cooling rate increases to about two thirds of the critical cooling rate, massive crystallization behavior is not observed, showing that the crystallization occurred in the HAZ in the process of preparing BMGs with SLM can be suppressed with a critical temperature variation rate.